THE IMPLICATIONS AND IMPACT OF BREXIT - Čavoški, Aleksandra (Pravni zapisi, 2019)
Following the referendum held on 23 June 2016, the UK Government, in accordance with Article 50 TEU, notified the president of the European Council of its intention to leave the European Union. The decision of the UK to leave the EU known as “Brexit” has presented both the EU and the UK with complex challenges. While it is almost impossible to predict and assess all the effects of Brexit, the author identifies in this short overview the most important challenges facing both parties to the negotiations, as well as assesses the wider implications of Brexit on future EU enlargement. The effects of Brexit in the UK are much deeper and long-lasting than in the EU. These include deepening political and social cleavages, economic effects and the need for comprehensive legal reform. Despite the initially gloomy prospects about the future of the European Union, the EU gradually reaffirmed its authority among member states and returned to ‘business as usual’. With regard to wider impacts of Brexit, in particular on the enlargement process, the paper will argue that though the effects of Brexit are gradually diminishing, the EU is firmly committed to building a stronger sense of shared values among its current and prospective members.